Motor performance of badminton teenage athletes - Browne, Rodrigo Alberto Vieira (2013)
The aim of this study was to identify and classify physical fitness for neuromuscular performance and muscle-bone health of badminton adolescent athletes from the state of Piauí. To this end, 50 badminton teenagers athletes from the Federal Institute of Piauí, being 25 boys [16.0 (15.6-17.01) years old, BMI= 21.6±2.3 kg.m-2] and 25 girls [15.0 (14.9-15.4) years old, BMI= 20.9±2.6 kg.m-2] were underwent to physical fitness tests for neuromuscular performance and bone-muscle health, and subsequently classified as suggested by Project Sport Brazil (PROESP-BR), in which were evaluated the explosive strength of upper limbs (FEMS), explosive strength of lower limbs (FEMI) velocity (VEL), agility (AGIL), flexibility (FLEX) and muscular endurance -abdominal (RML). Boys had significantly higher (p<0.05) than girls for FEMS (514.3±59.3 vs. 354.4±44.5 cm; p=0.0001), FEMI [211.0 (192.2-220.7) vs. 154.0 (49.8-165.8) cm; p=0.0001], RML (41±11 vs. 31±7 repeats; p=0.0001), VEL [3.44 (3.38-3.68) vs. 4.16 (4.01-4.31) s; p=0.0001] and AGIL [5.78 (5.64-6.11) vs. 6.76 (6.52-7.03) s; p=0.001]. Nevertheless, no significant difference was observed (p<0.05) between sexes for FLEX. On the other hand, compared the frequency of subjects in strata grading (Poor, Fair, Good, Very Good and Excellent) for variables FEMS, FEMI, VEL and AGIL, there were no significant differences in the frequencies of strata between the sexes. However, for the FLEX, girls have a higher prevalence of subjects in the area of health risk (p=0.012). In conclusion, badminton adolescents athletes of male sex, seem be stronger, agile, fastand resistant than their female peers. In addition, girls had a higher frequency of subjects in stratum of health risk for this variable FLEX.